2020
DOI: 10.1002/lary.29006
|View full text |Cite
|
Sign up to set email alerts
|

Organic vs. Inorganic Tracheobronchial Airway Foreign Body Aspiration: Does Type/Duration Matter?

Abstract: Objective We sought to determine the time course of clinical and histologic differences between aspirated inorganic and organic foreign bodies. Study Design In‐vivo. Methods Twenty Sinclair miniature swine (Sus scrofa domesticus) were divided into two groups—inorganic or organic foreign bodies. Either an organic (peanut) or an inorganic (Lego) foreign body was placed within a bronchus and left for 3, 5, 7, 14 or 21 days. The airway was reassessed at the predetermined endpoint at which time endoscopic, gross, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 18 publications
1
15
1
Order By: Relevance
“…We also found a correlation between the retention time of TFBA and LRTI. In our study the incidence of LRTI was 46.6%, 68.6% and 68.6% respectively with the retention time of within 24 hours, one week and more than one week,which was consistent with the results of a previous animal experiment 9 . In this animal experiment, it was found that most of the TFBA could cause tracheal damage within 5 days, and pneumonia more than 5 days.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…We also found a correlation between the retention time of TFBA and LRTI. In our study the incidence of LRTI was 46.6%, 68.6% and 68.6% respectively with the retention time of within 24 hours, one week and more than one week,which was consistent with the results of a previous animal experiment 9 . In this animal experiment, it was found that most of the TFBA could cause tracheal damage within 5 days, and pneumonia more than 5 days.…”
Section: Discussionsupporting
confidence: 92%
“…It is controversial whether there is a difference in the degree of trachea inflammation caused by the type of TFBA. Although it has been reported that the intratracheal granulation in TFBA is related to the degree of TFBA oil release 17 , no correlation was found in animal experiments 9 . As for age, we speculate that the immunity of younger children is relatively weak so that they are easier to get LRTI when encounter the same TFBA.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…When diagnosing atypical foreign bodies in the trachea of infants and young children, it is necessary to use X-rays for chest plain radiographs and fluoroscopy to determine the presence of foreign bodies through indirect signs. However, when the imaging manifestations such as pulmonary obstruction, pulmonary block shadows, and atelectasis occur, it is easy to be misdiagnosed as bronchial pneumonia, bronchial lung cancer, bronchial asthma, and other diseases, and the misdiagnosis rate is high [ 5 ]. Ordinary CT axial images increase the detection rate of foreign bodies, and the display clarity of indirect lung signs is better than X-ray, but it has the disadvantages of slow scanning speed, only presenting axial images, and easy to miss small foreign bodies.…”
Section: Introductionmentioning
confidence: 99%